ANALISIS KINERJA KEUANGAN DAERAH MENGGUNAKAN RASIO KEUANGAN PADA ANGGARAN PENDAPATAN, BELANJA, DAN PEMBIAYAAN DAERAH (APBD) (Studi Pada Laporan Keuangan Pemerintah Daerah (LKPD) Kabupaten Sukoharjo Periode 2015-2024) - Isnaini Nur Azizah; Haryanto Haryanto (Diponegoro Journal of Accounting, 2026)
This research aims to evaluate the regional financial performance of Sukoharjo Regency over ten years (2015–2024) using a financial ratio approach across revenue, expenditure, and financing sectors. The research methodology uses secondary data from BPKPAD financial reports, processed using a descriptive-quantitative approach with analytical instruments, including variance, growth, effectiveness, efficiency, and harmony ratios, along with a financing analysis of SiLPA and Reserve Funds. The results indicate that Sukoharjo Regency maintains a high level of fiscal dependency on the central government, characterized by the dominance of Transfer Revenues in the regional budget (APBD) structure, averaging 74.49% relative to the contribution of Regional Original Revenue (PAD), with a fiscal independence ratio of only 30.21%. In terms of expenditure, the study identifies fiscal rigidity, marked by a massive dominance of Operating Expenditure, which reached a peak of 87.91% in 2024, while Capital Expenditure was at its lowest point at 12.07%. Although budget absorption is considered highly efficient, with a 94.44% ratio, the excessive volume of routine spending has created liquidity pressures in the financing sector. This is empirically supported by a negative growth trend in SiLPA of -25.15% and a consistent year-over-year decline in the Reserve Fund balance. Furthermore, the impact of the COVID-19 pandemic during 2020–2022 exacerbated this structural imbalance through refocusing policies that hindered long-term infrastructure investment. This research concludes that a structural reform of expenditure and the optimization of fiscal independence are imperative to ensure the sustainability of regional development.